Evaluation of Dental Caries Experience and Biofilm Accumulation in Mexican Pediatric Patients with Autism Spectrum Disorder (ADS): A Cross-Sectional Study - Esparza-Loredo, Susana (2026)
Autism Spectrum Disorder (ASD) presents sensory and behavioral challenges that may complicate oral care. This study evaluated biofilm accumulation and caries prevalence in children with and without ASD, enrolled in an educational center in San Luis Potosí, México. A cross-sectional study was conducted at a specialized ASD educational center in San Luis Potosí, México. Twenty children with ASD and 40 neurotypical children, matched by age and sex, underwent oral examinations assessing biofilm using the simplified debris index (DI-S) and caries using the international caries detection and assessment system (ICDAS). Participants aged 5-12 years(90%male). Caries prevalence was significantly lower in the ASD group (60%) compared with controls (95%) (p=0.01). DI-S scores indicated fair-to-poor oral hygiene in both groups, with no significant differences. Early ICDAS lesions (codes 1-2) were more common in ASF primary teeth, whereas cavitated lesions (codes 3-6) were more frequent in neurotypical children. In this study population of children with ASD demonstrated lower caries prevalence yet similar biofilm accumulation compared with neurotypical peers.